The Effectiveness of Growth and Development Feedback Sheets on Increasing the Knowledge, Attitudes and Skills of Midwives in Providing Growth and Development Education for Toddlers Tangerang - Kasmayanti, Septi; Nurlatifah HR, Teni; Anwar, Ruswana (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Children who experience non-optimal growth and development have an impact on emotional, behavioral, educational achievement and health problems in the future, one of the efforts to improve the level of child welfare by stimulatingearly detection of child growth and development. The purpose of the study was to determine the effectiveness of the use of growth and development feedback sheets on increasing the knowledge, attitudes and skills of midwives inproviding growth and development education for children under five in Tangerang City. The research method used wastrue experimental with the form of the randomized pretest and posttest control group design. midwife research sample. The sampling technique used random sampling totaling 72 people. the intervention group was given a growth anddevelopment back sheet as many as 36 respondents and the control group was given the SDIDTK book as many as 36 respondents. Bivariable analysis was done with correlation test and man whitney. The results of the study knowledge r=0.035 (<0.05), attitude r=0.000 (<0.05), skills r=0.000 (<0.05). The growth and development worksheet ismore effective than the SDIDTK book with an N-Gain calculation of 80.13%, which means it is effective. Themultivariate results of Pillai's trace obtained a value of r= 0.000 so that there is an effectiveness of the growth and development back sheet on increasing the knowledge, attitudes and skills of midwives in providing growth anddevelopment education.